Reproductive cycle and gonad development of the Northern Argentinean Mesodesma mactroides (Bivalvia: Mesodesmatidae) - Herrmann, Marko; Fernandez Alfaya, Jose Elias; Lepore, Mauro L.; Penchaszadeh, Pablo Enrique; Laudien, Jurgen
The reproductive cycle and gonad development of the yellow clam Mesodesma mactroides was studied over a period of 24 months (January 2005?December 2006) at the Argentinean sandy beach Santa Teresita. Histological examination of gonadal tissue revealed that sex ratios did not significantly deviate from the proportion of 1:1 and no case of hermaphroditism was found. The reproductive cycle of M. mactroides followed an annual cyclicality, which was significantly correlated to monthly mean sea surface temperatures (SST). Oocytes showed highest abundance in winter, indicating a process of gonadal development and sexual maturation. The mean oocyte size decreased significantly during spring. Modal oocyte sizes decreased significantly during winter and late spring of each year, suggesting spawning events. The condition index was not useful in describing the annual reproductive cycle of M. mactroides. Ash-free, shell-free dry mass was chosen to detect the condition of the specimens, and this significantly correlated with monthly mean SST and the gametogenic cycle. Annual recruitment patterns during summer?autumn indicated a 3-month-long planktonic phase of M. mactroides. The reproduction cycle and gonad development of M. mactroides showed only weak differences between data from the present study and those collected 40 years ago. Fil: Herrmann, Marko. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina. Alfred Wegener Institute for Polar and Marine Research; Alemania Fil: Fernandez Alfaya, Jose Elias. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Lepore, Mauro L. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino ...